2014
DOI: 10.1185/03007995.2014.982751
|View full text |Cite
|
Sign up to set email alerts
|

How effective are the ESC/EAS and 2013 ACC/AHA guidelines in treating dyslipidemia? Lessons from a lipid clinic

Abstract: The application of the ACC/AHA guidelines may be associated with undertreatment of high risk patients due to suboptimal LDL-C response to high-intensity statins in clinical practice. Adding ezetimibe substantially increases the rate of the ESC/EAS LDL-C target achievement together with the rate of LDL-C lowering response suggested by the ACC/AHA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 22 publications
2
33
0
Order By: Relevance
“…Indeed, recently a retrospective (from 1999 to 2013) observational study including 1,000 consecutive adults treated for hyperlipidaemia and followed up for ≥ 3 years compared the applicability of current European and US guidelines and concluded that the application of the US guidelines may be associated with undertreatment of high-risk patients due to suboptimal LDL-C response to high-intensity statins in clinical practice. This study also found that adding ezetimibe to a statin substantially increased the rate of the European guidelines LDL-C target achievement together with the rate of LDL-C lowering response suggested by the US guidelines [45].…”
Section: What To Do With Statinsupporting
confidence: 56%
“…Indeed, recently a retrospective (from 1999 to 2013) observational study including 1,000 consecutive adults treated for hyperlipidaemia and followed up for ≥ 3 years compared the applicability of current European and US guidelines and concluded that the application of the US guidelines may be associated with undertreatment of high-risk patients due to suboptimal LDL-C response to high-intensity statins in clinical practice. This study also found that adding ezetimibe to a statin substantially increased the rate of the European guidelines LDL-C target achievement together with the rate of LDL-C lowering response suggested by the US guidelines [45].…”
Section: What To Do With Statinsupporting
confidence: 56%
“…23 We have previously shown that the use of ezetimibe in addition to statins improves LDL-C target attainment proposed by the European Society of Cardiology/European Atherosclerosis Society (ESC/EAS) guidelines, a target difficult to achieve even in the setting of specialized lipid clinics. 12 Moreover, the achievement of LDL-C reduction by $50%, as proposed for high-risk individuals by the American College of Cardiology/American Heart Association (ACC/AHA) guidelines, is more frequently accomplished with the combination of statin plus ezetimibe, rather than with the use of high-intensity statin monotherapy. 12 Although ezetimibe is a commonly prescribed hypolipidemic agent, there are no adequate data regarding the effect of ezetimibe on glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…12 Briefly, we included dyslipidemic adults attending the Outpatient Lipid Clinic of the University Hospital of Ioannina in Greece and followed-up for at least 3 years. All participants had a complete assessment of concomitant diseases and their treatment.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6] We have previously reported that even in the setting of a lipid clinic, only one out of four very high risk patients achieved the optimal LDL-C target < 70 mg/dL and 42% of those at high CV risk had LDL-C < 100 mg/dL. [4,7] In the US, 31% of the hypertensive individuals and 36% of those with diabetes do not reach the BP and glycemic targets, respectively. [5,6] Data are limited regarding the rates of goal achievement of lipid-lowering, antihypertensive and antidiabetic treatment in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] In two previous publications, we presented data for the lipid goal achievement of patients attending a Lipid Clinic of a University Hospital. [4,7] In this report, we studied only the older outpatients and present data for LDL-C target attainment, but also for BP and glycemic control. In addition, the rates of the less strict BP and glycemic target achievement, recently recommended in the elderly, [2,10] were recorded along with the incidence of treatment side effects.…”
Section: Introductionmentioning
confidence: 99%